Disease severity and proton pump inhibitor use impact strongest on faecal microbiome composition in liver cirrhosis - Stadlbauer, Vanessa (Liver Int, 2020)
BACKGROUND & AIMS: Compositional changes of the faecal microbiome in cirrhosis are well described and have been associated with complications and prognosis. However, it is less well known, which disease or treatment‐related factors affect microbiome composition most distinctively. METHODS: 16S rDNA sequencing data of 88 cirrhotic outpatients were investigated. Factors influencing microbiome composition were analysed by univariate and multivariate redundancy analysis. The association of the identified factors with changes in diversity and taxonomic composition was studied in depth using analysis of composition of microbiome, LDA‐effect size and least absolute shrinkage and selection operator regularized regression. RESULTS: Disease severity and aetiology, proton pump inhibitor (PPI) use, nutritional status, age and C‐reactive protein are significant explanatory variables for faecal microbiome composition in liver cirrhosis. Despite some taxonomic overlaps especially between disease severity and PPI use, we could show that the effects of disease severity, aetiology, PPI use and age are independent factors influencing microbiome composition also in subgroup analyses. CONCLUSION: Our cross sectional system biology study identifies disease severity, aetiology, PPI use and age as independent factors that influence microbiome composition in liver cirrhosis. In chronic diseases with high morbidity, such as liver cirrhosis, precise patient metadata documentation is of utmost importance in microbiome analysis. Further studies with a higher sample size are necessary to validate this finding. Trial Registration Number: NCT01607528